Karakuri : paper made to move - Borgert-Spaniol, Megan, 1989- (Abdo Publishing, 2020)
Karakuri will introduce kids to the Japanese art of making movable models out of paper. They will learn how to make a frog that hops, a gymnast that swings, and more!
Includes bibliographical references (page 31) and index.
Keywords: Paper art -- Juvenile literature; Origami -- Juvenile literature; Paper work -- Juvenile literature